Earning Growth in Indonesian Food and Beverage Companies: - , Zulkifli; Dewi , Cynthia Sari (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The objective of the research is to investigate the relationship between financial ratios (current ratio, return on assets, debt to equity ratio) and earning growth in consumer non-cyclical companies within the food and beverage industry listed on the Indonesia Stock Exchange. Design/methodology/approach: The research employed a quantitative approach using secondary data from audited financial reports spanning from 2019 to 2022 sourced directly from the Indonesia Stock Exchange website. The sample of 18 consistent companies through purposive sampling over a 4-year period, combining time series and cross-sectional data in a panel regression analysis. Research Findings: The adjusted R-squared value indicates that the three variables (current ratio, return on assets, debt to equity ratio) collectively contribute 10.38% to earning growth. The F-test shows that the combined effect of current ratio, return on assets, and debt to equity ratio is significant on earning growth. The hypothesis tests found that Current ratio does not significantly affect earning growth, Return on assets has a positive and significant impact on earning growth, Debt to equity ratio does not significantly influence earning growth Theoretical Contribution/Originality: The study indicates that return on assets has a significant positive effect on earning growth, while current ratio and debt to equity ratio do not have significant impacts. Keywords: earning growth, current ratio, return on asset, debt to equity ratio